2014
DOI: 10.2478/s11696-014-0610-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhizofiltration potential of Arundo donax for cadmium and zinc removal from contaminated wastewater

Abstract: The main aim of the presented work was to design and characterize the rhizofiltration system comprised of giant reed plants (Arundo donax L.), as species with phytoremediation potential, for the removal of cadmium as a toxic metal and zinc as an important microelement from model solutions spiked with radionuclides 109 Cd and 65 Zn. The possibility of effective cadmium and zinc rhizofiltration by the root system of giant reed plants under continuous flow conditions to achieve complete decontamination was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Islam et al [95] reported the phytofiltration capability of Micranthemum umbrosum to remove Cd and arsenic (As) from a hydroponic system. In another experiment, the rhizofiltration potential of Arunda donax for Zn and Cd removal, it and recommended the use of the rhizofilteration technique for Cd elimination [96].…”
Section: Phytofiltrationmentioning
confidence: 99%
“…Islam et al [95] reported the phytofiltration capability of Micranthemum umbrosum to remove Cd and arsenic (As) from a hydroponic system. In another experiment, the rhizofiltration potential of Arunda donax for Zn and Cd removal, it and recommended the use of the rhizofilteration technique for Cd elimination [96].…”
Section: Phytofiltrationmentioning
confidence: 99%
“…Overall, the genus Phragmites is one of the most effective plants in removing pollutants from wetlands [46]. For the other plant bioindicators, the literature review revealed metals to be assimilating in shoots and roots of Aruno donax and Nasturtium officinale indicating their strong phytoremediation potential [47,48]. Although some studies observed Nasturtium officinale to have a threshold for uptake of metals such as Pb, Cd and As [49].…”
Section: Percent Of the Types Of Waste The Plants Treatedmentioning
confidence: 99%
“…In contrast, rhizofiltration primarily employs the roots of certain terrestrial or aquatic plant species to absorb, concentrate, and precipitate HMs from contaminated water and aqueous waste sources. By using rhizofiltration, numerous plant species have been found to effectively remove HMs such as Pb, Cd, Cu, Ni, Zn, and Cr, which are primarily held within the roots and has been proven to be suitable for the treatment of acid mine drainage, partially treated industrial discharges and agricultural runoff, as well as low-level radioactive contaminants from liquid streams [12].…”
Section: Phytoremediation and Mechanisms Of Applicationmentioning
confidence: 99%